2004
DOI: 10.1177/002215540405200512
|View full text |Cite
|
Sign up to set email alerts
|

Tensin Is Expressed in Glomerular Mesangial Cells and Is Related to Their Attachment to Surrounding Extracellular Matrix

Abstract: S U M M A R Y Glomerular expression of tensin was immunohistochemically studied in normal and diseased rat kidneys to determine whether tensin might be related to specific binding in individual glomerular cells. Normal rat kidneys displayed an intense immunofluorescence reaction for tensin along the basal aspects of proximal and distal tubule cells and parietal epithelial cells of Bowman's capsules. In glomeruli, a positive reaction for tensin was detected only in the mesangial areas. Immunoelectron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Treatment with PTK/ZK down-regulated not only ␣-SMA but also tensin expression. The latter protein was shown to be expressed at the mesangial protrusions, 38 similarly to ␣-SMA. 12 Tensin is hypothesized to be an important molecule for the contractile apparatus of mesangial cells.…”
Section: Possible Implications Of Mesangial ␣-Sma and Tensin Down-regulation By Ptk/zk: Presence Of Intraglomerular Hemorrhages Reduced Nmentioning
confidence: 97%
See 1 more Smart Citation
“…Treatment with PTK/ZK down-regulated not only ␣-SMA but also tensin expression. The latter protein was shown to be expressed at the mesangial protrusions, 38 similarly to ␣-SMA. 12 Tensin is hypothesized to be an important molecule for the contractile apparatus of mesangial cells.…”
Section: Possible Implications Of Mesangial ␣-Sma and Tensin Down-regulation By Ptk/zk: Presence Of Intraglomerular Hemorrhages Reduced Nmentioning
confidence: 97%
“…12 Tensin is hypothesized to be an important molecule for the contractile apparatus of mesangial cells. 38 Overexpression of ␣-SMA and tensin during nephritis could therefore allow mesangial cells to better support vessels that recover from injury, and when this phenotypic change is prevented by PTK/ZK, mesangial cells lose their specific features and let endothelium be fully vulnerable to antiangiogenic therapy. Indeed, the vascular casting method, which is in fact the cast of endothelial cells covering the lumen of perfused vessels, showed that glomerular capillary surface is malformed and tortuous.…”
Section: Possible Implications Of Mesangial ␣-Sma and Tensin Down-regulation By Ptk/zk: Presence Of Intraglomerular Hemorrhages Reduced Nmentioning
confidence: 99%
“…The TNS studied in this work was presumably TNS1. TNS expression in glomerular mesangial cells was related to adhesion to the surrounding ECM and possibly the production of ECM molecules by the same cells . Which TNS was studied is unclear.…”
Section: Functionmentioning
confidence: 99%
“…Meanwhile, TNS2 mRNA levels are similar between glomeruli and non-glomeruli in the kidney, and CTEN is not detectable [ 42 ]. At the protein level, TNS1 is most concentrated at the proximal and distal tubules in the cortex region, as well as Bowman’s capsules and mesangial cells in glomeruli by immunohistochemistry staining [ 37 , 42 , 43 ]. Immunohistochemistry staining shows that TNS2 proteins are expressed at the podocytes, mesangial cells, tubules, collecting ducts, and renal pelvis epithelia, whereas TNS3 proteins are present at the podocytes, tubules, collecting ducts, and renal pelvis epithelia [ 42 ].…”
Section: Tensin Expressions In the Kidneymentioning
confidence: 99%